Relationships between leader’s emotional intelligence, transformational leadership style and outcomes on subordinates - Ang, Jianyong (2008)
The purpose of this research is to investigate firstly, the relationships between the individual dimensions in workplace emotional intelligence and transformational leadership behaviours. Next, this research also investigated the role of transformational leadership style as a moderator between emotional intelligent leaders and selected meaningful desired outcomes.